2017
DOI: 10.3389/fpls.2017.01170
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage and Association Mapping of Halo Blight Resistance in Common Bean to Race 6 of the Globally Important Bacterial Pathogen

Abstract: Pseudomonas syringae pv. phaseolicola (Psph) Race 6 is a globally prevalent and broadly virulent bacterial pathogen with devastating impact causing halo blight of common bean (Phaseolus vulgaris L.). Common bean lines PI 150414 and CAL 143 are known sources of resistance against this pathogen. We constructed high-resolution linkage maps for three recombinant inbred populations to map resistance to Psph Race 6 derived from the two common bean lines. This was complemented with a genome-wide association study (GW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 72 publications
3
40
1
Order By: Relevance
“…The Pse-2 gene, conferring resistance to races 2, 3, 4, 5, 7, 8 and 9, was previously linked in repulsion to the Pse-1 gene for resistance to races 1, 5, 7 and 9 [ 6 ], but the linkage distance between Pse-1 and Pse-2 has not yet been discerned. Recently, Tock et al [ 47 ] mapped a major-effect QTL for the races 2, 7, 8, and 9 on LG10 that overlaps the one reported here (3.411–3.457 Mb), and concluded that it corresponds to race-specific loci Pse-2 . This may indicate that UI3 contains an alternative race-specific resistance allele to the one mapped by Tock et al [ 47 ] and that is tightly linked but is functionally distinct from the race-specific Pse-2 gen.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The Pse-2 gene, conferring resistance to races 2, 3, 4, 5, 7, 8 and 9, was previously linked in repulsion to the Pse-1 gene for resistance to races 1, 5, 7 and 9 [ 6 ], but the linkage distance between Pse-1 and Pse-2 has not yet been discerned. Recently, Tock et al [ 47 ] mapped a major-effect QTL for the races 2, 7, 8, and 9 on LG10 that overlaps the one reported here (3.411–3.457 Mb), and concluded that it corresponds to race-specific loci Pse-2 . This may indicate that UI3 contains an alternative race-specific resistance allele to the one mapped by Tock et al [ 47 ] and that is tightly linked but is functionally distinct from the race-specific Pse-2 gen.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, Tock et al [ 47 ] mapped a major-effect QTL for the races 2, 7, 8, and 9 on LG10 that overlaps the one reported here (3.411–3.457 Mb), and concluded that it corresponds to race-specific loci Pse-2 . This may indicate that UI3 contains an alternative race-specific resistance allele to the one mapped by Tock et al [ 47 ] and that is tightly linked but is functionally distinct from the race-specific Pse-2 gen. The Pse-1 gene was completely linked to the SCARs markers SH11.800 and ST8.1350 [ 5 ], but the localization of these markers based on their sequence homology with the reference genome ( ; ) is very distant, 11.18 and 40.99 Mb, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Renewed efforts could mirror, to an extent, what the dedicated international centre did back during the 70 s and 80 s, by creating a panel of common accessions for phenotypic screening, and for development of populations with shared molecular information. Such steps are critical also in the development of mapping populations, linkage mapping, and Genome Wide Association Studies (GWAS) for trait discovery, as shown in soybean (Li et al 2018), chickpea (Bajaj et al 2016;Saeed and Darvishzadeh 2017), mung bean (Noble et al 2018), and common bean (Tock et al 2017). This would allow us also to combine phenotypic and genetic data across different environments and assess the degree of adaptability and plasticity of winged bean.…”
Section: Future Directionsmentioning
confidence: 99%